Molecular and histopathological analysis of peripheral ameloblastoma of the mandible mimicking a papillomatous lesion on the buccal mucosa. Issue 3 (May 2022) - Izumi, Sayaka; Komiyama, Yuske; Shimura, Michiko; Sawatani, Yuta; Oshima, Ryo; Zama, Mamabu; Fukumoto, Chonji; Kamimura, Ryouta; Yaguchi, Erika; Wakui, Takahiro; Nakashiro, Koh-ichi; Uchida, Daisuke; et al.
Abstract: An 89-year-old woman visited our hospital requesting the examination of a papillary mass in the posterior region of the right buccal mucosa. The orthopantomography and contrast-enhanced CT images showed a mass lesion existing near the mandibular ramus toward the muscular process, the posterolateral maxilla and the temporal fossa. The boundary of the lesion was unclear. Biopsy was taken twice and the general pathologists tentatively diagnosed the lesion as papilloma. However, since the lesion seemed invasive, we and an oral pathologist suspected the lesion as possibly invasive tumor, and surgical resection was performed. The histopathological diagnosis of the surgical specimen was a mixed lesion of plexiform- and acanthomatous-type ameloblastoma. Immunohistochemistry revealed CK19 (-), CK7 (-), p16(+), Ber-EP4(-), which supported the diagnosis as ameloblastoma. Possible mutations of BRAF and PTCH1 was suggested by whole exome sequencing. By accumulating the histopathological, immunohistochemical and genetical investigations, we may be able to lead an accurate diagnosis for odontogenic tumors, and a further planning of the treatment.